Free field realizations of certain modules for affine Lie algebra slˆ(n,C) - Martins, R.A. (Algebra and Discrete Mathematics, 2011)
For the affine Lie algebra slˆ(n,C) we study a realization in terms of infinite sums of partial differential operators of a family of representations introduced in [BBFK]. These representations generalize a construction of Imaginary Verma modules [F1]. The realization constructed in the paper extends the free field realization of Imaginary Verma modules constructed by B.Cox [С1].